A 10-year review of obstetrics anal sphincter injury at a tertiary teaching hospital in the east coast of Peninsular Malaysia/ Ahmad Amir Ismail ... [et al.] - Ismail, Ahmad Amir; Ibrahim, Adibah; Ismail, Mohd Pazudin; Nik Lah, Nik Ahmad Zuky; Johan Noor, Shah Reza; Mohamad Zon, Erinna; Wan Adnan, Wan Fadhlina; Yaacob, Najib Majdi; Engku Husna, Engku Ismail (Faculty of Medicine, 2023)
Introduction: Obstetric anal sphincter injury (OASIS) is an uncommon complication that may occur during vaginal delivery and increases the risk of pelvic floor dysfunction following delivery. This 10-year review is aimed to determine the occurrence of OASIS at a tertiary teaching hospital. Methods: A retrospective review of records of women who had their newborns delivered at Hospital Universiti Sains Malaysia between 2007-2016 was conducted. OASIS was classified according to the classification proposed by Sultan AH in 1999. Women who delivered on the same day with the index delivery but without OASIS acted as the control group (n = 154). Results: There were 61,049 vaginal deliveries over the ten years. A total of 154 women were recorded to have vaginal delivery complicated with OASIS, with a cumulative prevalence of 0.25% per year. Of these, 86% (n = 133) sustained a third-degree, and the remaining 14% (n = 21) had a fourth-degree perineal tear. Three independent risk factors for OASIS were identified using multivariable analysis: primiparity, greater gestational age, and higher infant birth weight. Conclusion: Nulliparous, primiparous, and a higher infant birth weight > 3500 g pose a higher possibility of developing OASIS during vaginal delivery among women who delivered at a tertiary teaching hospital on the east coast of Malaysia.